The effects of acute aerobic exercise on choice reaction time in young adults - Patil, Supriya Komalsingh; Patkar, Umesh Suresh; Patkar, Kshitija Umesh (International Journal of Research in Medical Sciences, 2017)
Background:Exercise, especially aerobic exercise thought to have a positive impact on cognitive and brain function which mainly involved in acquisition, processing, storage and executive functions. Executive control processes are important in sport and occupational settings where a person is being asked to make decisions while performing physical work. We have done this study, to determine the effects of acute moderate intensity exercise on cognitive domains and to apply this knowledge in various fields where cognition and executive functions are important. Study and control population each consists of 60 apparently healthy subjects in the age group of 18-30 years. Methods:The material used for study Cosco Upright Exercise Bike and Reaction Time apparatus. Visual Choice Reaction Time, the examiner presented visual stimuli at random to the subject. The subject saw the light displayed on his side and pressed the appropriate corresponding button as quickly as possible and the reading was noted. The same procedure was repeated for auditory choice reaction time for auditory stimuli. After that each subject from study population underwent acute moderate intensity aerobic exercise on for 10 minutes. Starting within 5 minutes after the exercise, subjects were assessed for the same cognitive test as above, for the second time. Control population rested for 10 minutes and then was assessed again for the same cognitive test. Results:There was no significant difference between the pre- values of study population and pre- values of control population. There was no significant difference between the pre- values of control population and post values of control population. Thus, there was no improvement in cognitive functions on account of repetition of tests. There was a significant difference between the post values of study population and post values of control population. There was a significant difference between the pre- values of study population and post values of study population. Conclusions:There was a decrease in reaction time following exercise in the study population, suggests that there was an improvement in the cognitive functions post exercise.